ChemInform Abstract: Theoretical Treatment of One Electron Redox Transformation of a Small Molecule Using F‐Element Complexes. Issue 40 (30th September 2014) - Castro, Ludovic; Kefalidis, Christos E.; McKay, David; Essafi, Stephanie; Perrin, Lionel; Maron, Laurent
Abstract Review: 62 refs.